The Principle of Equality Before the Law in Indonesian Corruption Case: Is It Relevant? - Moh. Iqra Syabani Korompot; Sholahuddin Al-Fatih; David Pradhan (Journal of Human Rights, Culture and Legal System, 2021)
Article 28D paragraph (1) of the NRI Constitution of 1945 states that "Everyone is entitled to the recognition, guarantee, protection, and certainty of fair law and equal treatment before the law". Unfortunately, the implementation of the article is not in accordance with the theory. Cases that go against the principle of equality before the law include cases of corruption convicts who get lavish facilities in poor prisons. The purpose of this research to find out the form of facilities obtained by corruption inmates is reviewed from the principle of equality before the law, as well as the extent of the government's efforts in dealing with cases like this. The methodology used to resolve this error uses empirical juridical research methods. Data collection techniques by conducting interviews, observations, documentation and re-analysis with qualitative methods that aim to understand phenomena occurring in the field. The results showed that the form of facilities obtained by corruption inmates such as televisions, cell phones, air conditioners made it easier to get in and out of prisons, and so on. The Government's efforts in dealing with this are to revitalize the coaching of inmates and the revised plan of Law no. 12 of 1995 on correctional with the aim of improving the personality quality of inmates until the presence of the intention to improve themselves and do not want to repeat the validity.